The Need of ESP Course in Communicative Speaking Skill - Ratna Muntiningsih (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
ESP course design model specifically in communicative speaking skill is very assential to be applied at vocational schools (SMK), because the students of these schools are prepared to work. In this case they have to know English well especially speaking. Moreover, ESP course approach designed based on the two fundamental principals mainly theoretical and pragmatics, and some of supported theories as well. Research objective is to know if the students of vocational schools which become a selected research is SMK Pariwisata Kosgoro at Jl Perjuangan Cirebon, are eager to accept that ESP course is one of their needs, in order they can improve their English particularly in communicative speaking skill. Meanwhile, the used research method is quantitative one.